Application of low-intensity anticoagulation after On-X mechanical aortic valve replacement - Kun Zou; Dachuang Wei; Bo Xiang; Tao Yu; Keli Huang; Shengzhong Liu (Journal of Cardiothoracic Surgery)
Abstract Objective To explore the safety and efficacy of low-intensity anticoagulation in patients after On-X mechanical aortic valve replacement. Methods A total of 104 patients undergoing aortic valve replacement in Cardiac Surgery Department of Sichuan Provincial People’s Hospital from December 2018 to December 2021 were randomly divided into low-intensity anticoagulant (INR:1.5-2.0) and high-intensity anticoagulant (INR:2.0-2.5) to compare the incidence of adverse events related to postoperative anticoagulation between the two groups. Results Fifty-three patients were included in the low-intensity anticoagulation group (INR 1.5-2.0), and 51 patients were included in the high-intensity group (2.0-2.5). There was no significant difference in baseline data and surgical index between the two groups (P > 0.05); there were statistically significant differences in PT, INR and bleeding events (P < 0.05), but no significant difference in embolic events (P > 0.05). Conclusion For patients requiring On-X mechanical aortic valve replacement who have no risk factors for thromboembolism, it is appropriate to control the INR in the target range 1.5-2.0, which can reduce the incidence of bleeding adverse events and significantly improve the quality of life, without increasing the risk of thromboembolic adverse events.